2017
DOI: 10.1242/jcs.198978
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of NFATc1 and NFATc4 in human primary myoblast differentiation and in the maintenance of reserve cells

Abstract: Ca signaling plays a key role during human myoblast differentiation. Among Ca-sensitive pathways, calcineurin is essential for myoblast differentiation and muscle regeneration. Nuclear factor of activated T-cell (NFAT) transcription factors are the major calcineurin targets. We investigated the expression and the role of each NFAT gene during human primary myoblast differentiation. We found that three NFAT isoforms are present, NFATc1, NFATc3 and NFATc4. Importantly, while their mRNA expression increases durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Notably, statistical significance was observed for the Solei genes, Sirt1 , Mef2c , and Vegf‐a , in the PEMF‐treated alone (–E/+P) cohort relative to controls (–E/–P), whereas exercised mice, with (+E/+P) or without (+E/–P) PEMF treatment, were not statistically different from sham controls (–E/–P). MEF2C promotes PGC‐1α expression 23,46,55‐57 and correlates with NFATC1 expression pattern 36,58 that precedes and predicts oxidative muscle development 59 . SIRT1 stimulates PGC‐1α expression, upstream of mitochondriogenesis and metabolic balance 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, statistical significance was observed for the Solei genes, Sirt1 , Mef2c , and Vegf‐a , in the PEMF‐treated alone (–E/+P) cohort relative to controls (–E/–P), whereas exercised mice, with (+E/+P) or without (+E/–P) PEMF treatment, were not statistically different from sham controls (–E/–P). MEF2C promotes PGC‐1α expression 23,46,55‐57 and correlates with NFATC1 expression pattern 36,58 that precedes and predicts oxidative muscle development 59 . SIRT1 stimulates PGC‐1α expression, upstream of mitochondriogenesis and metabolic balance 11 .…”
Section: Resultsmentioning
confidence: 99%
“…3, A and B). Myogenin is a common marker of myoblast differentiation that is regulated by the calcineurin-NFAT axis (2,42). Other indicators of differentiation were also increased in Ng siRNA cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, NFATs activities are frequently regulated by the PKAcalcineurinsignalling pathway during cell differentiation 33,34,35,36 . Indeed, NFATc2 primarily controlled myoblast recruitment and myoblast fusion 37,38,39,40 . Similarly, we found that the inhibitory effect of myoblast fusion by knockdown of Ezrin could be restored by the overexpression of NFATc2, but not NFATc1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that NFATc2 could perform speci c role in MyHC-2a and MyHC-2X expression with synergistic effect of MyoD while NFATc1 promoted MyHC-1 expression through inhibiting MyoD signaling 37,40 . More, NFATc4 has shown the inhibitory role in myoblast fusion 38 , and appears to mostly contribute to fast muscle ber formation, especially MyHC-2b 30 . The overexpression of NFATc4 affects the differentiation process by decreasing the expression of late differentiation markers, including MEF2c, and impairs myotube formation 30,38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation